Reformasi Prosedural Pengujian Peraturan Perundang-Undangan di Mahkamah Agung dalam Perspektif Keterbukaan dan Due Process of Law - Yoel Edward Hasugian (JURNAL ILMIAH NUSANTARA, 2026)
Judicial review of regulations below statutes by the Supreme Court of Indonesia plays a crucial role in safeguarding the hierarchy of laws and controlling executive regulations that have broad public impact. However, the procedural design of such judicial review has long been characterized by closed, document-based mechanisms with limited participation and transparency, raising concerns regarding the fulfillment of open justice and due process of law as minimum requirements for the legitimacy of erga omnes decisions. This study aims to examine whether the procedural design and practice of judicial review at the Supreme Court have met these principles and to formulate rational and constitutional procedural reforms without altering the Court’s authority. This research employs normative legal research methods using statutory, conceptual, and case-based approaches, supported by content analysis of selected judicial review decisions. The findings reveal that although procedural requirements are formally satisfied, judicial review at the Supreme Court remains procedurally minimalistic, non-deliberative, and insufficiently transparent, resulting in limited procedural justice and weakened normative legitimacy. To address this deficit, the study proposes procedural reforms consisting of limited open hearings, mandatory written and selective oral hearings, and minimum standards of legal reasoning, which can be implemented through amendments to Supreme Court Regulations and internal institutional policies. This study contributes to constitutional law scholarship by shifting the focus of judicial review discourse from authority-based debates to procedural legitimacy and demonstrates that strengthening due process and procedural openness is essential to enhancing the accountability and rationality of judicial review without expanding judicial power. Future research is encouraged to integrate empirical approaches to assess the effectiveness of procedural reforms and their impact on public trust in the judiciary.